Implementation of Edge Coupled Bandpass Filter on MnM Interposer - Tapia, Luis A. S. [UNESP]; Bernardo, Helton; Serrano, Ariana L. C.; Rehder, Gustavo P.; Ribeiro, Raul O. [UNESP]; Da Rosa, Guilherme S. [UNESP]; Aldaya, Ivan [UNESP]; Penchel, Rafael A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2024)
This work presents an edge-coupled band-pass filter on a metallic-nanowire membrane (MnM) interposer for 60 GHz millimeter-wave (mmW) applications. The MnM interposer, utilizing nanoporous copper technology, serves as a substrate for 3D integrated circuits, enabling efficient interconnections in system-on-chip (SoC) designs. The proposed filter achieves wideband operation with simulated and measured impedance bandwidths of 6.70 GHz and 7.74 GHz, respectively, and insertion losses of 3.14 dB and 3.65 dB at 60 GHz.
Keywords: 3D integrated circuits; coupled-line filter; millimeter-wave (mmW); MnM-interposer; systems-on-chip